2011
DOI: 10.1002/elps.201000466
|View full text |Cite
|
Sign up to set email alerts
|

Continuous‐time random walk models of DNA electrophoresis in a post array: Part I. Evaluation of existing models

Abstract: Several continuous-time random walk (CTRW) models exist to predict the dynamics of DNA in micropost arrays, but none of them quantitatively describes the separation seen in experiments or simulations. In Part I of this series, we examine the assumptions underlying these models by observing single molecules of λ DNA during electrophoresis in a regular, hexagonal array of oxidized silicon posts. Our analysis takes advantage of a combination of single-molecule videomicroscopy and previous Brownian dynamics simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 15 publications
(59 citation statements)
references
References 37 publications
3
54
2
Order By: Relevance
“…This concordance further underscores the quality of the simulation model, as evidenced in previous work. 18 While we expect that the device should continue to reach unity resolution at a reasonable length even up to 50 V/cm, we did not observe the exponential decay in the required time as a function of electric field that was seen in simulations. 24 Rather, to within the experimental error, the time required to reach R ¼ 1 should be approximately 300 s. This is clearly much improved over the untilted post array, which requires around 10-15 min to reach the same resolution for this range of molecular weights.…”
Section: B Comparison With Brownian Dynamics Simulationscontrasting
confidence: 52%
See 3 more Smart Citations
“…This concordance further underscores the quality of the simulation model, as evidenced in previous work. 18 While we expect that the device should continue to reach unity resolution at a reasonable length even up to 50 V/cm, we did not observe the exponential decay in the required time as a function of electric field that was seen in simulations. 24 Rather, to within the experimental error, the time required to reach R ¼ 1 should be approximately 300 s. This is clearly much improved over the untilted post array, which requires around 10-15 min to reach the same resolution for this range of molecular weights.…”
Section: B Comparison With Brownian Dynamics Simulationscontrasting
confidence: 52%
“…In the latter cases, the analytes tend to move at an angle with respect to the driving force, a method known as deterministic lateral displacement. 54 Since the DNA loses memory of its previous transport upon collision with a post, 18 it is not deflected by the post and thus does not exhibit deterministic lateral displacement. Rather, the separation proceeds in a manner similar to the separation in a conventional post array, with the DNA all moving in the direction of the applied voltage drop.…”
Section: Comparison With Other Tilted Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Brownian dynamics simulations that included the perturbations in the electric field caused by insulating posts matched the experimentally measured electrophoretic mobility [17,18], indicating that the disturbance in the electric field due to the posts qualitatively alters the transport in this relatively tight array. These experiments and simulations showed that DNA makes enough collisions in an ordered array to yield a size based separation [19].…”
mentioning
confidence: 58%